EMPLOYEE PERFORMANCE AND WORK MOTIVATION MODELS: TRANSFORMATIONAL LEADERSHIP AND WORK ENVIRONMENT - Chintya Ones Charli; Hapzi Ali (Jurnal Ipteks Terapan : research of applied science and education, 2023)
This study aims to uncover the influence of transformational leadership and the work environment on employee performance with work motivation as an intervening variable. The research was conducted at PT Abisiat Raya. The study population is 90 employees who work at PT Abisiat Raya. This study uses a saturated sample technique where the total population is less than 100 people and will be taken from the entire population. The number of samples is taken as a whole. Structural equation modeling (SEM) with a partial least square (PLS) approach is applied as a data analysis method. The study's results revealed that transformational leadership affects work motivation but cannot affect employee performance. The work environment does not affect work motivation or employee performance. And work motivation is known to affect employee performance. And there is an indirect influence between transformational leadership on employee performance through work motivation as an intervening variable. This research provides input to PT Abisiat Raya to improve the performance of its employees by improving transformational leadership and the work environment without neglecting the importance of motivation work.